Praktik Ruang Kolaborasi Ekonomi Sirkular pada Kasus Industri Tekstil di Kota Pekalongan - Aprilianna, Yohana; Pratama, Isnu Putra (Jurnal Dinamika Ekonomi Pembangunan, 2025)
The textile industry plays a role in boosting city economic growth, but in practice, it contributes to environmental pollution. The concept of a circular economy can be an alternative approach to overcome these problems. The case study in this study is Studio Sejauh, which plays a leading role as one of the initiators of the circular economy concept in Pekalongan City. The purpose of this research is to explore circular-economy collaboration practices that can increase the textile industry's added value in Pekalongan City. This study uses a qualitative approach, with data collected through interviews, observations, questionnaires, and document analysis. The analysis used was qualitative descriptive analysis, coding analysis, and Social Network Analysis (SNA). In its production chain, Studio Sejauh applies the 9R strategy (Refuse, Rethink, Reduce, Reuse, Repair, Refurbish, Remanufacture, Repurpose, Recycle, and Recover). Moreover, play a role in sustainable urban development. Implementing the Circular Economy creates value for the product, as seen from economic, environmental, and social perspectives. In practice, Studio Sejauh collaborates with textile industry players, especially in Central Java. This collaboration is an important factor in realizing a circular economy because it can provide greater results. The study found that aligned goals were the primary drivers of collaboration. The results of this research can enrich the literature on circular economy collaboration, serve as a basis for translating circular economy practices into the textile industry, and serve as a reference for other industry players to adopt similar practices.